Proliferative events and apoptotic remodelling in retinal development of common toad (Bufo bufo). Issue 1 (6th November 2015) - Pinelli, Claudia; Sansone, Alfredo; De Maio, Anna; Morgillo, Antonietta; Scandurra, Anna; D'Aniello, Biagio
ABSTRACT: Proliferation and apoptosis are fundamental processes in the development of the retina, and a proper balance of the two phenomena is crucial to correct development of the organ. Despite intense investigation in different vertebrates, only a few studies have analyzed the cell death and the cell division quantitatively in the same species during development. Here we studied the time course of apoptosis and proliferation in the retina of common toad, Bufo bufo, and discuss the findings in an evolutionary perspective. We found cells that were dividing first scattered throughout the retina, then, in later stages, proliferation was confined to the ciliary marginal zone. This pattern was confirmed by the expression of the proliferative marker PCNA. Both proliferation and apoptosis occurred in successive waves, and two apoptotic peaks were detected: one at premetamorphosis 1 and the second at prometamorphosis. PARP‐1, a known molecular marker of apoptosis, was used to confirm the data obtained by counting pyknotic nuclei. In summary, proliferative and apoptotic waves display an inverse time‐relationship through development, with apoptotic peaks coinciding with low proliferation phases. In a comparative perspective, amphibians follow a developmental pattern similar to other vertebrates, although with different timing. J. Exp. Zool. (Mol. Dev. Evol.) 326B:19–30, 2016 . © 2015 Wiley Periodicals, Inc.